Transformational leadership and its reflection on marketing crisis management : An exploratory study of the opinions of a sample of five-star hotel managers in the Dohuk city - Dawood, Dalia; Hameed, Hogir; Jameel, Farhad (Humanities Journal of University of Zakho, 2023)
The research aims to determine the role of transformational leadership through its dimensions (ideal impact, inspiration, mental stimulation, empowerment) on crisis management, especially marketing, according to the viewpoint of a group of managers in the hotel sector within the scope of Dohuk Governorate, where the research relied on a set of assumptions that were tested On (55) respondents, the data were collected through a questionnaire that was specially prepared to suit the research variables based on the statistical methods available in the (Spss.24) program to analyze the correlation and impact relationship between the variables. Awareness of managers in dealing with employees and developing highly accurate plans in dealing with marketing crises